Clinical profile and outcomes analysis of HIV infection - Ashwant Kumar; Yoganathan Chidambaram; Clement J. Dhas; Nekkanti Abilash; Murali Alagesan (HIV & AIDS Review. International Journal of HIV-Related Problems)
Background India has the third largest number of human immunodeficiency virus (HIV) patients, but the national prevalence is continuously receding owing to dedicated health centers as well as highly active antiretroviral therapy (HAART), which is associated with newer manifestations and outcomes. Complete understanding of HIV paradigm would facilitate timely identification, intervention, and medical modulation to obtain maximum benefits with minimal side effects. The study aimed to analyze the clinical profile and disease outcomes of HIV patients.